A retrospective institutional study for age determination by the root length of mandibular third molar on panoramic radiograph in deutero malay subject - Belly Sam; Ristaniah R. Effendy; Suhardjo Sitam; Ira Komara; Whildy A. Rifdah; Fahmi Oscandar (Journal of Dentomaxillofacial Science, 2022)
Objective: This study aimed to produce formula age determination by the root length of mandibular third molar on panoramic radiograph in Deutero Malay subject. Material and Methods: The analytical study design was done with 130 mandibular third molars on 90 panoramic radiographs of the Deutero Malay subject from patients who visited the Oral and Maxillofacial Radiology Unit at Dental Hospital Universitas Padjadjaran, Bandung, Indonesia. The inclusion criteria were patients in the age range between 15 to 21 years, panoramic radiograph with good quality, and the root of the mandibular third molar is still developing. The panoramic radiograph with the teeth showed root anomaly, dental pathology, and malposition as bucco-linguoangular were excluded. The root length of the third molar was measured from CEJ – root apex in millimeters following by Thevissen's modified scoring method using Fiji ImageJ-Win64. The simple linear regression of statistical IBM software was used to analyze the result. The reliability of the observers was evaluated to know the observer's variability. Results: There was a very strong correlation between the root length of mandibular third molar and chronological age for male (R=0.949) with formula chronological age = 11,847 + 0,459 (Root Length), (R2=0.901), (SEE=0.692), and for female (R=0.946) with formula chronological age = 13,701 + 0,410 (Root Length), (R2=0.895), (SEE=0.622). Conclusion: The root length of the mandibular third molar on a panoramic radiograph can be used for age determination in Deutero Malay subjects.